Metabolic characteristics of the body of athletes specializing in judo during anaerobic loading - Chystiakova, M.; Sovtisik, D.; Ladyniak, A.; Honshovskyi, V.; Hurman, L.; Marchuk, V.; Marchuk, D.; Makarchuk, B.; Tereschenko, O.; Berezhok, S. (Physical Education Sports and Human Health, 2023)
Judo is a physically demanding sport that requires a combination of strength, speed, agility, and endurance. While aerobic fitness is important for sustaining activity over a longer period of time, anaerobic fitness is also crucial for judo athletes, as the sport involves explosive movements and short bursts of intense activity. The purpose of the study: to evaluate the peculiarities of metabolic changes in the body of female athletes who specialize in judo, when performing anaerobic loads in different phases of the menstrual cycle Material and methods of research. The achievement of the goal envisaged solving the set tasks using a set of methods, including general scientific, practical and methods of mathematical statistics. The analysis of special scientific and methodical literature included printed literary sources and databases Scopus, SPORT Discus, Web of Science, Scholar. In total, more than 70 sources of information were analyzed, after which a final review was conducted and 30 literature sources were singled out, the material of which was processed using general scientific methods. Biochemical parameters of blood were studied - the content of glucose and lactate in the blood using the «Accutrend Plus» analyzer (Switzerland). The results. It was established that during the test load of anaerobic orientation in different phases of the menstrual cycle, a greater metabolic stress of the body of female athletes was noted both in the postovulatory phase, and at the same time, better results, which indicates a greater metabolic capacity of glycolysis, and in the menstrual and premenstrual phases, which are characterized by the stress of functioning regulatory mechanisms. Conclusions. The obtained results make it possible to purposefully influence the training process of female athletes who specialize in judo, to expand their reserve capabilities, to make adjustments to the training process in order to increase special work capacity.